Performance Analysis of ANODR and ZRP protocol against Wormhole attack in Wireless Sensor Network (International Journal of Engineering and Computer Science, 2018)
Wireless sensor network consist of spatial distributed sensor nodes deployed in a hostile and dense environment to gather information and propagate it to the base station for further processing. In the insecure wireless transmission medium, the enemies can analysis the data traffic against intercept-able routing information embedded in routing data packets. Allowing adversaries to trace network routing information and other critical information at the end of those routes may pose a serious threat to covert operations. Wireless sensor network has limited resources like bounded storage space, energy and computation power. In this paper, to prevent the network from wormhole attack, the ANODR, an anonymous on-demand routing protocol is implemented. The wormhole attack is one of the severe attack on WSN that can effect the networks performance. In this, attackers create a low-latency link between two points in the network. The wormhole attack tunnels the packets from one end to another end by modifying or altering its content. For route anonymity problem, the ANODR prevents strong adversaries from tracing a packet flow back to its originator and for location privacy problem, ANODR ensures that adversaries cannot discover the real identities of authenticated transmitters. The architecture of ANODR is based on technique named "broadcast with trapdoor information". The qualnet 4.5.1 simulator is opted to analyze the performance of ANODR on the basis of metrics like frame tunneled, frame dropped and intercepted.